Financial Burden of Households on the Treatment of Malaria in Southern Nigeria - Adesope, Adejare A.A.; Yusuf, Wasiu A.; Fawole, O. Oluseyi; Yusuf, A. Sulaiman (NIU Journal of Social Sciences; Vol 9 No 2 (2023): NIU Journal of Social Sciences, Vol. 9 No. 2, June 2023DO - 10.58709/niujss.v9i2.1631, 2023)
The number of deaths attributed to malaria is highest in Nigeria when compared with other countries of the world. This study estimated the monetary expenditure of households in Southern Nigeria in the treatment of malaria as well as the income forgone as a result of incapacitation due to the ailment. The study employed the cost-of-illness approach to estimate the financial burden of malaria treatment using the data contained in the Harmonized National Living Standard Survey (HNLSS) 2010. More cases of malaria were reported among children aged under-five while immunity increases with age up till age 45. Females, farming households and rural residents were also more vulnerable than their respective counterparts. The pattern of the distribution of direct and indirect cost was mixed across the three zones in the study area. Malaria poses both health and financial challenges to households. The financial burden of malaria is too high for a country like Nigeria whose majority of her citizens wallow in poverty. The drug subsidy policy of government has to be reviewed in order to increase the awareness of the public of its availability at subsidized rate. Massive public education on the importance of prevention as against treatment as well as the importance of seeking prompt treatment will also go a long way in ameliorating the indirect burden of malaria which forms a larger proportion of the total burden of malaria to households. Keywords: Cost burden, Cost of illness approach, Direct and indirect costs, Incapacitation, Malaria